Serious hypernatraemia in a hospital population. Issue 752 (June 1988) - Bhatnagar, D.; Weinkove, C.
Abstract : Severe hypernatraemia in a hospital population should be an avoidable problem. We have looked at its causes and incidence over one year and have shown that serious hypernatraemia (serum sodium greater than 160 mmol/l) as a manifestation of severe dehydration is associated with a high morbidity and mortality. Failure to maintain adequate fluid intake, intentional or unintentional, was the most frequent cause. Nursing and medical staff must be made more aware of this problem and encouraged to initiate early treatment of dehydration.